Arginine-stabilized mPEG-PDLLA (50/50) polymeric micelles of docetaxel by electrostatic mechanism for tumor-targeted delivery. (February 2015) - Shi, Jifeng; Zhang, Jialin; Shen, Yan; Tang, Lidan; Zhao, Jin; Tu, Jiasheng; Tian, Yu; Feng, Yanli
Abstract: Arginine-stabilized, docetaxel-loaded polymeric micelles (AR-DTX-PM) were prepared to enhance the physical stability of micelles and control the degradation of docetaxel (DTX). Amphiphilic diblock copolymers, methoxy-(Polyethylene Glycol)-block-Poly (D, L-lactide) (mPEG-PDLLA) were synthesized and used for the formulation of lyophilized DTX-PM powders. The micelles were found to have diameters of 20–30 nm with narrow polydispersity, and the entrapment efficiency was 90–100%. The accumulative release of AR-DTX-PM was higher than that of glucose-dispersed DTX-PM (Glu-DTX-PM). The results of both physical and chemical stability studies showed that the concentration of arginine required for optimum stability was 2.0 mg/ml. Preliminary investigation of the mechanisms of stabilization by arginine suggested that it is due to the electrostatic interaction as well as hydrogen bonds between DTX and arginine. The acute toxicity studies demonstrated that AR-DTX-PM was better tolerated in beagle dogs than DTX injection. However, the pharmacokinetic studies revealed no significant difference in Cmax and AUC of AR-DTX-PM compared to DTX injection. When AR-DTX-PM was administrated at a dose of 30 mg/kg, the antitumor effect was stronger than that of commercial DTX injection at 10 mg/kg, and the increase of administration dose did not cause higher toxicity. The in vivo imaging test showed that the residence time of AR-DTX-PM at tumor sites was longer than its commercial formulation. In a word, it is expected that AR-DTX-PM can reduce systemic toxicity while retaining antitumor efficacy in cancer patients.